Surface electromagnetic waves in left-handed material slab embedded in plasmalike media - Galaydych, V.K.; Azarenkov, N.A.; Olefir, V.P.; Sporov, A.E. (Вопросы атомной науки и техники, 2014)
This study is devoted to the dispersion properties of the electromagnetic surface eigen waves that propagate along the left-handed planar slab that is bounded by the air (vacuum) and the medium with positive plasma-like permittivity. Both the left-handed slab and the media are assumed to be isotropic and have zero losses. We present the results of the studying the phase and group velocities of the considered waves. Изучены свойства собственных поверхностных электромагнитных волн, распространяющихся вдоль плоской волноводной структуры, состоящей из слоя левостороннего материала, ограниченного вакуумом, и плазмоподобной средой с диэлектрической проницаемостью, зависящей от частоты. Слой левостороннего материала и окружающие среды предполагаются изотропными и бездиссипативными. Представлены результаты изучения фазовой и групповой скоростей рассматриваемых волн. Вивчено дисперсійні властивості власних поверхневих електромагнітних хвиль, які поширюються в пласкій хвилеводній структурі, яка складається з шару лівостороннього середовища, що межує з вакуумом та плазмоподібним середовищем з діелектричною проникливістю, яка залежить від частоти. Шар лівостороннього матеріалу та оточуючі середовища вважаються ізотропними та бездисипативними. Представлено результати дослідження фазової та групової швидкостей хвиль, що вивчаються.